An Unusual Case of Cervical Cancer with Inguinal Lymph Node Metastasis: A Case Report and Review of the Literature - Yavas, Guler; Ata, Ozlem; Celik, Cetin (Archives of Clinical and Medical Case Reports, 2017)
There is limited data regarding to treatment of cervical cancer patients with isolated non-regional lymph node metastasis. Herein we report a case of cervical cancer with left inguinal lymph node metastasis at the time of diagnosis. A 52-year-old woman referred to gynecologic oncology department with postmenopausal vaginal bleeding history for a year. Gynecological examination revealed a bulky cervical tumor with left parametrial invasion. The biopsy of this lesion revealed a squamous cell carcinoma of the cervix. A pelvic magnetic resonance imaging (MRI) demonstrated a bulky cervical mass with a parametrial extension on left side, in addition to the suspicious lymph nodes in the para-aortic, pelvic and left inguinal chains. The patient was underwent extraperitoneal para-aortic lymph node dissection and left inguinal lymphadenectomy. Histopathological examination of the lymph nodes revealed that there were metastatic lymph nodes in the para-ortic, and left inguinal chains. We planned neoadjuvant chemotherapy consisting of paclitaxel and carboplatin; and we decided to plan adjuvant treatment with respect to the treatment response to the induction chemotherapy. The control computed tomography after 6 cycle of chemotherapy showed that there was a good-partial response; therefore definitive radiotherapy was planned. A month after the radiotherapy pelvic MRI was performed and it showed a complete response. After 38 months of follow-up the patient admitted to the emergency department with ileus. The patient developed sepsis and forty months after the completion of the radiotherapy the patient expired because of septic shock.